Evaluation of microtextural properties of sourdough wheat bread obtained from optimized formulation using scanning electron microscopy and image analysis during shelf life - Hayta, M.; Hendek Ertop, M. (Springer Science and Business Media LLC, 2017)
The aim of this study was to evaluate the microtextural properties of optimized wheat bread formulation consisting sourdough (A) prepared with two different fermentation methods [spontaneous fermentation (F1) versus starter of lactic acid bacteria added fermentation (F2)], instant active dry yeast (B) and wheat bran (C) during shelf life. The optimized levels for F1 were 11.45 g 100 g-1 for sourdough, 1.10 g 100 g-1 for dry yeast and 1.58 g 100 g-1 for wheat bran and for F2 6.99 g 100 g-1 for sourdough, 1.02 g 100 g-1 for dry yeast and 38.84 g 100 g-1 for wheat bran. The addition of sourdough significantly decreased the diameters of starch granules of sourdough breads, and affected shape and surface apparance of starch granules. The retrogradation phenomena during storage was explained with the change of interaction between starch granules and protein matrix. The F1 fermentation method was found to be more effective in terms of bread textural properties examined.
Keywords: 2. Zero hunger; 3. Good health